Ice road : vengeance [videorecording (DVD)] - Hensleigh, Jonathan; Neeson, Liam; Fan, Bingbing, 1981-; Thomas, Marcus (Actor); O'Sullivan, Grace; Sharma, Saksham; Curry, Bernard, 1974-; Morrell, Geoff, 1958-; Jadu, Mahesh; Bishop, Amelia (Actor); Batliwalla, Shapoor; Anand, Monish; et al. (Vertical Entertainment, 2025)
"Big rig ice road driver Mike McCann travels to Nepal to scatter his late brother's ashes on Mt. Everest. While on a packed tour bus traversing the deadly 12,000 ft. terrain of the infamous Road to the Sky, McCann and his mountain guide encounter a group of ruthless mercenaries and must fight to save not only themselves but the innocent passengers and a local village on the brink of destruction."--